Identifying a reference list of respiratory sensitizers for the evaluation of novel approaches to study respiratory sensitization. (26th November 2021) - Sadekar, Nikaeta; Boisleve, Fanny; Dekant, Wolfgang; Fryer, Allison D.; Gerberick, G. Frank; Griem, Peter; Hickey, Christina; Krutz, Nora L.; Lemke, Olga; Mignatelli, Cecile; Panettieri, Reynold; Pinkerton, Kent E.; et al.
Abstract: The induction of immunological responses that trigger bio-physiological symptoms in the respiratory tract following repeated exposure to a substance, is known as respiratory sensitization. The inducing compound is known as a respiratory sensitizer. While respiratory sensitization by high molecular weight (HMW) materials is recognized and extensively studied, much less information is available regarding low molecular weight (LMW) materials as respiratory sensitizers. Variability of symptoms presented in humans from such exposures, limited availability of (and access to) documented reports, and the absence of standardized and validated test models, hinders the identification of true respiratory sensitizers. This review aims to sort suspected LMW respiratory sensitizers based on available compelling, reasonable, inadequate, or questionable evidence in humans from occupational exposures and use this information to compose a reference list of reported chemical respiratory sensitizers for scientific research purposes. A list of 97 reported respiratory sensitizers was generated from six sources, and 52 LMW organic chemicals were identified, reviewed, and assigned to the four evidence categories. Less than 10 chemicals were confirmed with compelling evidence for induction of respiratory sensitization in humans from occupational exposures. Here, we propose the reference list for developing novel research on respiratory sensitization.